The Evaluation of Zoomed Echo-Planar Diffusion-Weighted Magnetic Resonance Imaging With Two-dimensional Spatial-Selective Radiofrequency Excitation Pulses in Patients With Hilar Cholangiocarcinoma - Liu, Jingjing; Huang, Mengyue; Ren, Yanan; Xu, Man; Li, Yinhua; Cheng, Jingliang; Zhu, Jinxia (Frontiers in Oncology, 2022)
Background We aimed to investigate the feasibility and application of using the zoomed diffusion-weighted echo-planar imaging (z-EPI DWI) sequences for hilar cholangiocarcinoma assessment compared with conventional single-shot EPI diffusion-weighted imaging (c-EPI DWI). Methods Both c-EPI DWI and z-EPI DWI were preoperatively performed in 16 patients with histopathologically-confirmed hilar cholangiocarcinoma. A two-dimensional spatial-selective radiofrequency (RF) pulse was applied to the z-EPI DWI using an echo-planar transmit trajectory. Anatomic structural visualization, lesion conspicuity, artifact presence and overall image quality were evaluated and compared between the two sequence images. The ratio of differences regarding hilar cholangiocarcinoma lesion sizes measured on T2-weighted imaging (T2WI) and diffusion-weighted imaging (DWI) were compared from both EPI techniques. The DW images for tumor involvement of the bile duct were reviewed based on histopathological examination of the surgical intraoperative evaluation. ADC measurements of DWIs in the hilar cholangiocarcinoma lesions were conducted. Results The hepatic hilar region was better delineated by visualization of anatomical structures, lesion conspicuity and overall image quality using the z-EPI DWI and these analyses were compared with the c-EPI DWI method (all p<0.05). Better lesion delineation of bile duct walls and lumens was noted in four patients with z-EPI DWI compared with those of c-EPI DWI. No significant differences were noted between the two image datasets for artifacts (p=0.876). The ratio of differences regarding hilar cholangiocarcinoma lesion sizes was significantly lower (p= 0.018) on T2WI and DWI, as determined by the z-EPI DWI than that determined by the c-EPI method. The use of z-EPI DWI resulted in the accurate diagnosis of the Bismuth-Corlette classification of 15 tumors (15/16, 93.75%), whereas the use of c-EPI DWI resulted in correct diagnosis of 12 tumors (12/16, 75.00%). There were no significant differences between c-EPI DWI and z-EPI DWI in the ADC values of hilar cholangiocarcinoma lesions (p= 0.48). Conclusion z-EPI DWI resulted in remarkable image quality improvements for hilar cholangiocarcinoma. The ability to detect and delineate lesions using z-EPI DWI was superior to that of c-EPI DWI.